Molecular Evidence for the Broad Distribution of Anaerobic Ammonium-Oxidizing Bacteria in Freshwater and Marine Sediments - Penton, C. Ryan (American Society for Microbiology, 2006)
Previously available primer sets for detecting anaerobic ammonium-oxidizing (anammox) bacteria are inefficient, resulting in a very limited database of such sequences, which limits knowledge of their ecology. To overcome this limitation, we designed a new primer set that was 100% specific in the recovery of ∼700-bp 16S rRNA gene sequences with >96% homology to the “Candidatus Scalindua” group of anammox bacteria, and we detected this group at all sites studied, including a variety of freshwater and marine sediments and permafrost soil. A second primer set was designed that exhibited greater efficiency than previous primers in recovering full-length (1,380-bp) sequences related to “Ca. Scalindua,” “Candidatus Brocadia,” and “Candidatus Kuenenia.” This study provides evidence for the widespread distribution of anammox bacteria in that it detected closely related anammox 16S rRNA gene sequences in 11 geographically and biogeochemically diverse freshwater and marine sediments.